1991
DOI: 10.1128/iai.59.3.1172-1176.1991
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody immunotherapy in nude mice persistently infected with Cryptosporidium parvum

Abstract: Three groups of congenitally athymic nude mice were persistently infected following oral administration of 2 x 10(7) Cryptosporidium parvum oocysts. Two groups were treated once daily for 10 days with either neutralizing monoclonal antibody (MAb) 17.41 or an isotype control MAb. The third group received no treatment. Intestinal-infection scores were significantly decreased in nude mice treated with MAb 17.41 compared with isotype control MAb-treated and nontreated control groups (P less than 0.005). Biliary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…The utility of Abs in the control of intestinal cryptosporidiosis is exemplified by passive immunotherapy studies with polyclonal Abs and MAbs (reviewed in reference 31). Anti-C. parvum MAbs, and polyclonal Abs in hyperimmune hen egg yolk and secretory IgG1-rich hyperimmune bovine colostrum, have been efficacious in the control of intestinal cryptosporidiosis in immunologically immature or immunocompromised rodent models (1,5,9,12,25,26,32,34,37). Hyperimmune polyclonal Ab preparations have had variable efficacy against intestinal C. parvum infection in immunocompromised humans (24,39,40,42).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The utility of Abs in the control of intestinal cryptosporidiosis is exemplified by passive immunotherapy studies with polyclonal Abs and MAbs (reviewed in reference 31). Anti-C. parvum MAbs, and polyclonal Abs in hyperimmune hen egg yolk and secretory IgG1-rich hyperimmune bovine colostrum, have been efficacious in the control of intestinal cryptosporidiosis in immunologically immature or immunocompromised rodent models (1,5,9,12,25,26,32,34,37). Hyperimmune polyclonal Ab preparations have had variable efficacy against intestinal C. parvum infection in immunocompromised humans (24,39,40,42).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatobiliary cryptosporidiosis is a common complication in AIDS patients having persistent intestinal C. parvum infections (6,7,15,20,28,41,43). While oral Ab-based immunotherapy has shown efficacy against intestinal infection, this approach is unlikely to be effective against hepatobiliary cryptosporidiosis (5,25). Further, hepatobiliary cryptosporidiosis may provide a reservoir of infection which can contribute to relapse of intestinal infection following clearance with Ab-based immunotherapy (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the importance of immune responses in controlling C parvum infection, we and others have produced monoclonal antibodies (mAbs) that neutralize the infectivity of merozoites and/or sporozoites, the two infectious stages of the organism (2,5,22,26). Investigators have shown that these antibodies protect suckling mice from initial infection (2,5,20,22,26,28) and reduce the severity of persistent cryptosporidial infections in nude mice (4,19). Severe combined immune deficient (scid) mice infected with C. parvum have been used to study infection parameters and treatment protocols (14)(15)(16)24).…”
mentioning
confidence: 99%